An Innovative International Community Engagement Approach: Story Circles as Catalysts for Transformative Learning. (April 2018) - Maslin-Ostrowski, Pat; Drago-Severson, Eleanor; Ferguson, Janet; Marsick, Victoria J.; Hallett, Margaret
The purpose of this article is to describe the successes and challenges of an innovative community engagement initiative in Bermuda, Education for All, in order to enlarge our understanding of how a community uses storytelling as a catalyst for transformative learning. Sponsored by the Coalition for Community Activism, community members and nonprofit groups united to facilitate an islandwide conversation about the student experience. They aspired to transform how people think about what constitutes an appropriate education and, ultimately, reframe the Bermuda conversation of schooling. We trace the evolution of the project attending to how adults came together around a shared purpose and vision for improving education. In so doing, we illuminate the complexities of using story as a catalyst for transformative learning. We provide a story circle protocol developed to gather stories of public school alumni. This story project for social change has implications for community leaders globally.